The world of nano-biomechanics : mechanical imaging and measurement by atomic force microscopy - Ikai, Atsushi; Afrin, R. (Rehana) (Amsterdam ; Boston : Elsevier, 2008)
By using nanotechnological methods, we can now poke around protein molecules, genes, membranes, cells and more. Observation of such entities through optical and electron microscopes tempt us to touch and manipulate them. It is now possible to do so, and scientists around the world have started pulling, pushing and cutting small structures at the base of life processes to understand the effect of our hand work. The book describes the physical properties of such life supporting structures from the molecular level with a special emphasis on their designs based on the mechanical strength and flexibility, membrane and other biological nanostructures. - Describes the basic mechanical features of proteins, DNA, cell membrane and other biological nanostructures - Explains the basic concepts and mathematics of elementary mechanics needed to understand and perform experimental work.
Preface -- Chapter 1. Force in Biology -- Chapter 2. Introduction to Basic Mechanics -- Chapter 3. Force and Force Measurement Apparatuses -- Chapter 4. Polymer Chain Mechanics -- Chapter 5. Interaction Forces -- Chapter 6. Single Molecule Interaction Forces -- Chapter 7. Single Molecule DNA and RNA Mechanics -- Chapter 8. Single Molecule Protein Mechanics -- Chapter 9. Motion in Nano-biology -- Chapter 10. Cell Mechanics -- Chapter 11. Manipulation at the Molecular Level -- Chapter 12. Finite Element Analysis of Microscopic Biological Structures -- Chapter 13. Appendices.
Includes bibliographical references and index.
Keywords: Biomechanics; Nanostructures; Atomic force microscopy; Atomic force microscopy; Biomechanics; Nanostructures; Biomechanik; Nanotechnologie; Biomechanics; Electronic books